On one problem of minimization of area - Ligun, A. A.; Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the problem of asymptotically optimal location of disks with equal radii for the minimization of the are of the figure bounded by a given curve and a connected union of these disks.